Development and Validation of a Prognostic Gene Signature in Clear Cell Renal Cell Carcinoma - Zhan, Chuanchuan; Wang, Zichu; Xu, Chao; Huang, Xiao; Su, Junzhou; Chen, Bisheng; Wang, Mingshan; Qi, Zhihong; Bai, Peiming (Frontiers in Molecular Biosciences, 2021)
Clear cell renal cell carcinoma (ccRCC), one of the most common urologic cancer types, has a relatively good prognosis. However, the confirmed patients are mostly in the medium or late stages, when the mortality and recurrence rates are quite high. It’s necessary to conduct real-time information tracking, dynamic prognosis analysis for these patients. Hence, we downloaded the RNA-seq and corresponding clinical information of ccRCC from The Cancer Genome Atlas (TCGA) database and Gene Expression Omnibus (GEO) database. and 3238 differentially expressed genes were identified between normal and ccRCC tissues. Through series of Weighted Gene Co-expression Network, overall survival, immunohistochemical and the least absolute shrinkage selection operator (LASSO) analyses, seven prognosis-related genes (AURKB, FOXM1, PTTG1, TOP2A, TACC3, CCNA2, and MELK) were screened out and its risk score signature was constructed. Survival analysis indicated that high-risk scores had significantly worse overall survival than low-risk patients. The good accuracy of this prognostic signature was confirmed by the ROC curve analysis and was further validated in another cohort. Gene set enrichment analysis demonstrated some cancer-related phenotypes were significantly gathered in the high-risk group. Overall, our results demonstrate that this risk model could potentially improve individualized diagnostic and therapeutic strategies.